HUBUNGAN PENGETAHUAN IBU TENTANG DETEKSI DINI KANKER SERVIKS DENGAN PEMERIKSAAN PAP SMEAR DIPOLI OBGYN RSUP.H. ADAM MALIK MEDAN - Nababan, Tiarnida (Jurnal Keperawatan Priority, 2018)
Cervical cancer is one of the main causes of cancer death in women around the world today. Among gynecologic malignant tumors, cancer of the uterine cervix is ​​still ranked first in Indonesia and is a cause of death for Indonesian women. Cervical cancer is caused by infection with the HPV virus (Human Pappiloma Virus). The onset of this cancer occurs because most women do not want to do an early detection check with pap smears. Women do not want to be examined because of ignorance, fear, shame and economic factors. This is generally due to the low level of knowledge of the Indonesian population who do not understand the importance of pap smears. Pap smear examination is an attempt to take fluid from the vagina to see cell abnormalities around the cervix. Through pap smear examination, the precancerous stage until the cancer can be detected so as to allow treatment quickly and precisely. This study aims to determine the relationship of maternal knowledge about early detection of cervical cancer with pap smear examination in Obgyn Poly Hospital H. Adam Medan Hospital. This type of research is descriptive correlative with cross sectional approach. The population of the study were 71 mothers who visited poly obgyn as many as 71 mothers and a total sample of 60 mothers were taken by purposive sampling. Data collection was done using questionnaires and observations, then the research data was analyzed by chi-square statistical test value p = 0.05. Based on the results of data analysis it is known that there is a relationship between maternal knowledge about early detection of cervical cancer with pap smear examination and p value = 0.000 <0.05. Therefore, it is recommended for mothers who have not done pap smears to find information about pap smears from the media that have been provided from the government and actively participate in counseling especially about women's reproductive health.